Operation study phytase enzyme in substitute fish meal with soy meal in diet beluga (Huso huso) juvenile, on growth performance and carcass quality - Reza Asadi, Reza; Imanpoor, Mohamad Reza; Asghari, Masoud; Gholampour, Tayebe Enayat (2017)
In this experimental, effects of phytase enzyme and substitute fish meal with soy meal were studied in 8 weeks, on growth performance and carcass quality in beluga juvenile. The beluga juvenile (weight mean 80.65±2.16g) were distributed in 21 fibreglasses tank and feed with 7 diets that were contains different levels of soy and phytase. Experimental dietaries were prepared include control diet wherein was not use of soy meal and phytase enzyme and other 6 experimental dietaries in factorial method 2×3 include tow levels 70 and 40 percentage substitute fish meal with soy meal and three levels phytase (zero, 1000 and 2000 IU/kg). In the end growth tests, significant differences were found in growth performance (p<0.05). Biomass gain, specific growth rate and protein efficiency ratio in fish feed with control diet were significantly higher (p<0.05) and control treatment had the minimum feed conversion rate. However survival had not significant different. There were significant difference among substitute effect, phytaze enzyme effect and interaction (p<0.05). With increase substitute fish meal with soy meal and phytaze enzyme, growth performance had decrease and increase in sequence. There were no significant differences among moisture, protein, lipid and gross energy contents of dietary treatments. However ash content in control diet was lower than the other treatments (P<0.05). The substitute effect, phytase enzyme effect and interaction had not significant different among carcass quality. Published